Regional strategy for the control of African swine fever in Africa - Food and Agriculture Organization of the United Nations; African Union Interafrican Bureau for Animal Resources; International Livestock Research Institute (Food and Agriculture Organization of the United Nations, 2017)
The actual African evolution is characterized by a strong integration at regional level, resulting in intensive trade, accentuated the movements of people and free movement of goods and people. In this context, only a regional approach can be considered for reducing the risk of economic losses due to the ASF. This approach creates synergy between countries and benefits from the experience of each other. Despite the loss due to the disease and many actions taken to control the disease, the situation remains dramatic in terms of threat of livelihood of populations. The elaborated strategy joined with an action plan, allow a progressive and coordinated control of the disease at regional level. To achieve this objective, it prioritizes the strengthening of capacities of technical services and the improvement of current production systems, creating optimal conditions for the modernization and development of the pig industry in a healthy context.